Pengaruh Penggunaan Aplikasi E-Faktur, Aplikasi E-Bupot Dan Pemeriksaan Pajak Terhadap Kepatuhan Wajib Pajak Badan Di Kantor Pelayanan Pajak Madya Dua Jakarta Utara - Dedy Setiawan Priyohadi; Dian Wahyudin (Jurnal Pajak Vokasi (JUPASI), 2026)
Corporate taxpayer compliance remains a challenge at the Madya Dua Jakarta Utara Tax Office, as evidenced by the continued occurrence of late tax reporting and payment. This phenomenon underscores the importance of optimizing various tools such as the implementation of the e-Invoice Application, e-Bupot Application, and tax audits. This study aims to analyse the impact of the implementation of the e-Invoice Application, e-Bupot Application, and Tax Audits on corporate taxpayer compliance. The method used is quantitative research with a population of 206 corporate taxpayers and a sample of 67 respondents. The results of the study indicate that the implementation of the e-Invoice Application is in the moderate category with a significant influence on taxpayer compliance of 60.1% (t-calculated = 2.141 > t-table = 1.997), the e-Bupot Application is in the good category with a significant influence of 68.4% (t-calculated = 7.789 > t-table = 1.997), and Tax Audits are in the moderate category with a significant influence of 53.9% (t-calculated = 12.739 > t-table = 1.997). Simultaneously, the three independent variables have a significant effect on Taxpayer Compliance, with a correlation coefficient (r) of 0.749 indicating a strong relationship, and a determination coefficient (r²) of 0.561 or 56.1%. The F-test shows that F count is 58.462, which is greater than F table 3.14, so the multiple regression model used is significant. Keywords: e-invoice; e-bupot; tax audit; taxpayer compliance